Assessment of dental student studying strategies - Lindemann, R A; Cabret, M L (Journal of dental education, 1995)
This study evaluated the studying strategies of second-year and third-year dental students as related to end-quarter exam preparation. Focus groups were convened to elicit current student studying strategies that were incorporated into a three-question survey and administered to second- and third-year students. Strategic use of study resources was rank ordered in the first question; course characteristics influencing study prioritization were rank ordered in the second question; and a third question addressed strategic time management. Overall, both second- and third-year students ranked the studying resource "notepool" first, although students of high academic standing ranked "texts and syllabi" first. Regarding course characteristics, both classes gave high ranking to "instructor expectations," "performance on midterm," and "course structure." Second-year students rated "performance on midterm" as significantly more important to prioritization than did third-year students (p = 0.01, t-test). As to time management, a statistically significant number of second-year students (p < 0.01, chi-square) ranked "studying for exams mid-quarter" first while third-year students (p = 0.05) ranked "studying the week before finals" first. Second- and third-year students of high academic standing indicated that they began studying at the beginning of the quarter. The data suggest that studying strategies change as students progress in school and that students of high and low academic ranking differ in the strategies they employ.